Perbandingan Laju Penurunan Muka Tanah Menggunakan Metode DInSAR dengan Pengolahan Data Aktual - Annisa Amelia; Nia Kurniadin; Romansah Wumu; Shabri Indra Suryalfihra (Politeknik Pertanian Negeri Samarinda, 2023)
This research is motivated by how the data generated from the capabilities of the radar technology used in monitoring land subsidence using the DInSAR (Differential Interferometry Synthetic Aperture Radar) method is compared with actual data in the mining sector. The purpose of this study was to determine the suitability of the land subsidence rate using the DInSAR method against the actual data. DInSAR processing is carried out using a pair of Sentinel-1 Terrain Observation by Progressive Scans (TOPS) images with acquisition times before and after changes in conditions due to mining activities. Actual data processing in the form of topographical data at the End of the Month (EOM) by carrying out the drape elements process by 30 sample points to provide information on the value of changes in elevation that occur within a period of three months. The results of the research show that there is a discrepancy between the data generated using the DInSAR method and the actual data. This can be due to the limitations of radar sensors in detecting soil dredging activities in mining areas. So that further processing is needed so that the results of Sentinel-1 Image processing with the DInSAR method can represent the value of land subsidence in the field.